ChemInform Abstract: Site‐Selective Sonogashira Reactions of 1, 4‐Dibromo‐2‐(trifluoromethyl)benzene: Synthesis and Properties of Fluorinated Alkynylbenzenes. Issue 22 (3rd June 2014) - Reimann, Sebastian; Wittler, Kai; Schmode, Stella; Sharif, Muhammad; Fahrenwaldt, Thomas; Ludwig, Ralf; Spannenberg, Anke; Langer, Peter
Abstract Site‐selective Sonogashira reactions of 1, 4‐dibromo‐2‐(trifluoromethyl)benzenes is developed to provide practical routes for the synthesis of mono‐ and disubstituted alkynyl(trifluoromethyl)benzenes.